Caloric restriction favorably impacts metabolic and immune/inflammatory profiles in obese mice but curcumin/piperine consumption adds no further benefit. - Wang, Junpeng.; Vanegas, Sally M.; Du, Xiaogang.; Noble, Timothy.; Zingg, Jean-Marc A.; Meydani, Mohsen.; Meydani, Simin Nikbin.; Wu, Dayong. (2016)
Background: Obesity is associated with low-grade inflammation and impaired immune response. Caloric restriction (CR) has been shown to inhibit inflammatory response and enhance cell-mediated immune function. Curcumin, the bioactive phenolic component of turmeric spice, is proposed to have anti-obesity and anti-inflammation properties while piperine, another bioactive phenolic compound present in pepper spice, can enhance the bioavailability and efficacy of curcumin. This study sought to determine if curcumin could potentiate CR's beneficial effect on immune and inflammatory responses in obesity developed in mice by feeding high-fat diet (HFD).; Keywords: Obesity, Caloric restriction, Inflammation, T cells, Curcumin, Piperine.; Springer Open.